Ten simple rules to complete successfully a computational MSc thesis project. - Edoardo Saccenti; Cristina Furlan (PLoS Computational Biology)
The thesis project is an essential step to obtain an MSc degree. Within STEM and Life Sciences disciplines, computational theses have specific characteristics that differentiate them from wet laboratory ones. In this article, we present Ten simple rules to direct and support Master students who are about to start a computational research project for their Master thesis. We begin by recommending defining the personal learning goals for the project; we then highlight specific pitfalls that computational students might encounter during their work, such as procrastination by computation or wasting time while attempting to reinvent computational tools. We provide the students a series of suggestions on how to work following FAIR principles, learn new computing languages, and think ahead for computational challenges. We hope that these 10 simple rules will provide Master students with a framework for the successful completion of their computational thesis.